Restorative Justice Arrangements in Civil Law, Common Law, and Indonesian Legal Systems - Apituley, Lilian Gressthy Florencya; Baroto, Wishnu Agung; Soplantila, Valentino Dinatra (SASI, 2025)
Introduction: This article will outline how the application of restorative justice in the civil law system, the common law system, and the Indonesian legal system compares.Purposes of the Research: This study aims to provide a comprehensive comparison of the regulation and implementation of restorative justice across three legal systems - civil law, common law, and Indonesia’s hybrid legal system - and to identify best practices and challenges that can inform the development of restorative justice in diverse legal contexts.Methods of the Research: The study uses a normative legal method, combining a legal concept approach to examine the philosophical and ethical foundations of restorative justice with a statutory approach to analyze formal legal mechanisms. This methodology links legal theory with practice while highlighting the integration of normative principles within Indonesia’s socio-cultural context, including Pancasila and customary law.Results of the Research: This study compares restorative justice implementation in civil law, common law, and Indonesia’s legal system. Civil law is rigid and procedural, while common law allows flexible mechanisms such as victim–offender mediation. In Indonesia, despite Supreme Court Rule Number 1 of 2024, challenges include limited understanding among law enforcement, inconsistent application, and insufficient institutional support. Strengthening implementation requires harmonized regulations, professional training, community-based mechanisms rooted in local wisdom and customary law, and public awareness. Indonesia’s model highlights a transformative approach that integrates restorative principles with national values of humanity, justice, and social harmony.